Supporting reflective lesson planning based on inquiry learning analytics for facilitating students’ problem solving competence development: The inspiring science education tools - Zervas, P.; Sampson, Demetrios (2016)
© Springer Nature Singapore Pte Ltd. 2018. Science education is recognized as a top priority for school education reforms worldwide. Inquiry-based teaching strategies are recognized as appropriate for supporting the development of the cognitive processes that cultivate problem solving (PS) competence, a key competence of scientific literacy. A widely used framework for assessing individual students’ problem solving competence at large scale is PISA 2012 Problem Solving Framework (PSF). Nevertheless, PISA 2012 PS competence assessment is primarily summative and not connected to the daily school science teaching practice. On the other hand, school accountability and self-improvement requires evidence to relate students’ PS competence development to specific design considerations of lesson plans and their corresponding teaching and learning activities used in day-to-day school science inquiry-based teaching practice. Within this context, the scope of this book chapter is to present and discuss a set of tools which aim to support the authoring and delivery of technology-enhanced science education lessons, which follow an adaptation of the 5E model, while incorporating PISA 2012 PSF compatible assessment activities at each inquiry phases. These tools support science teachers in collecting inquiry learning data, namely data from students’ activities and students’ problem solving competence performance data at each stage of the inquiry process. The further analysis of those inquiry learning data can be used for evidence-based reflective lesson planning targeting to better support students’ problem solving competence development through inquiry-based teaching.